Peritoneal carcinomatosis after minimally invasive surgery versus open radical hysterectomy: systematic review and meta-analysis. Issue 12 (8th November 2022) - Hoegl, Jorge; Viveros-Carreño, David; Palacios, Tatiana; Gallego - Ardila, Andres; Rauh-Hain, Jose Alejandro; Estrada, Erick Estuardo; Noll, Florencia; Krause, Kate; Baiocchi, Glauco; Minig, Lucas; Grillo - Ardila, Carlos Fernando; Pareja, Rene
Abstract : Objective: To assess the incidence of peritoneal carcinomatosis in patients undergoing minimally invasive or open radical hysterectomy for cervical cancer. Methods: The MEDLINE (accessed through Ovid), Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Clinical Trials, and Scopus databases were searched for articles published from inception up to April 2022. Articles published in English were considered. The included studies reported on patients with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IA-IIA squamous cell carcinoma, adenocarcinoma, and/or adenosquamous carcinoma of the cervix who underwent primary surgery. Studies had to report at least one case of peritoneal carcinomatosis as a recurrence pattern, and only studies comparing recurrence after minimally invasive surgery versus open surgery were considered. Variables of interest were manually extracted into a standardized electronic database. This study was registered in PROSPERO (CRD42022325068). Results: The initial search identified 518 articles. After the removal of the duplicate entries from the initial search, two authors independently reviewed the titles and abstracts of the remaining 453 articles. Finally, 78 articles were selected for full-text evaluation; 22 articles (a total of 7626 patients) were included in the analysis—one randomized controlled trial and 21 observational retrospective studies. The most common histology was squamous cell carcinoma in 60.9%, and the tumor size was <4 cm in 92.8% of patients. Peritoneal carcinomatosis pattern represented 22.2% of recurrences in the minimally invasive surgery approach versus 8.8% in open surgery, accounting for 15.5% of all recurrences. The meta-analysis of observational studies revealed a statistically significant higher risk of peritoneal carcinomatosis after minimally invasive surgery (OR 1.90, 95% CI 1.32 to 2.74, p<0.05). Conclusion: Minimally invasive surgery is associated with a statistically significant higher risk of peritoneal carcinomatosis after radical hysterectomy for cervical cancer compared with open surgery.